TERAPI KOMPLEMENTER HERBAL SEBAGAI ALTERNATIF SOLUSI MERINGANKAN PMS (PRE MENSTRUASI SINDROM) PADA REMAJA PUTRI - Febriati, Listia Dwi; Rahayu, Puspito Panggih (Universitas Respati Yogyakarta, 2021)
Background: Women have special needs than men, women experience menstruation, pregnancy, childbirth and breastfeeding as well as menopause. hence women need more intensive care during their life cycle. Menstruation in women can experience Pre Menstrual Syndrome complaints. A complementary herbal therapy is one that can be used to reduce pain. Extension and training activities were carried out in the Village of Dhuku Jambidan. Based on information from several young women, they really need young women activities related to reducing menstrual pain, because menstrual pain from 5 teenage girls is very disturbing activities. The purpose of this service is expected to be able to increase the knowledge of young women about complementary herbal therapies to reduce complaints of Pre Menstrual Syndrome, and to provide provision to adolescents on how to make tamarind turmeric herbs to reduce pain. The method in this service is counseling and demonstration of herbal medicine. Result: there was an increase in knowledge before and after counseling, the young woman could also re-dominate the steps of making tamarind turmeric herbs.Keywords : Complementary; Herbs, PMS (Pre Menstrual Syndrome)Â